Experiences Of Occupational Therapists In Implementing The Who ICF Model For Disability Determination In Armenia - Ghazaryan, Tatevik; Iskandaryan, Laura; Babikian, V. Armineh; Kovic, Mark
In 2023, the Republic of Armenia officially transformed its previous disability assessment system to a new process based on the World Health Organization's (WHO) International Classification of Functioning, Disability, and Health (ICF) model. The purpose of this study is to identify and analyze the barriers faced by Occupational therapists when assessing the domains of activity and participation within the framework of the new ICF disability assessment process in Armenia and suggest improvement solutions. The methodology of this research study is based on a qualitative descriptive approach, as it provides in-depth insights into participants' experiences, perceptions, and meanings. The data collection method was semi-structured virtual interviews with six Occupational therapists working in the Administration of Person Functionality Assessment. Data analysis was conducted using thematic analysis. This study identified two categories of key factors affecting the disability assessment process - external (i.e., systemic) and internal (i.e., related to the therapists’ actions). External factors included coding inconsistencies, lack of standardized assessment tools, insufficient training for paramedical specialists, and the complexity of the assessment process, all of which hindered effective evaluations. Internal factors included limited professional experience in adult rehabilitation, lack of multidisciplinary collaboration, and the risk of influencing patient responses. These challenges highlight the need for multilevel interventions such as targeted professional development, increased availability of standardized tools for the Armenian context, and training related to multidisciplinary coordination of care to strengthen the assessment process.
Keywords: Psychology